2021
DOI: 10.3389/fnut.2021.784532
|View full text |Cite
|
Sign up to set email alerts
|

Saccharina japonica Ethanol Extract Ameliorates Depression/Anxiety-Like Behavior by Inhibiting Inflammation, Oxidative Stress, and Apoptosis in Dextran Sodium Sulfate Induced Ulcerative Colitis Mice

Abstract: Saccharina japonica is a common marine vegetable in East Asian markets and has a variety of health benefits. This study was focused on the anti-depressant/anxiety effects of Saccharina japonica ethanol extract (SJE) on dextran sodium sulfate (DSS)-induced mice and its potential mechanism in their brain. Male C57BL/6 mice were treated with mesalazine and various doses of SJE (1, 2, and 4 g/kg body weight) for 2 weeks, followed by DSS treatment at the second week. The DSS-induced mice showed depression/anxiety-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…It was also reported that there are links between anxiety, oxidative stress and neuron damage (19,20). Thus, we continued to investigate the central neuroprotective effect of nutrients.…”
Section: The Nutrient Combinations Showed Central Neuroprotective Eff...mentioning
confidence: 91%
“…It was also reported that there are links between anxiety, oxidative stress and neuron damage (19,20). Thus, we continued to investigate the central neuroprotective effect of nutrients.…”
Section: The Nutrient Combinations Showed Central Neuroprotective Eff...mentioning
confidence: 91%
“…The preparation method of SJE was performed according to Dong et al (2021) [ 13 ] with slight modifications. In short, saccharin is ground into a powder using a mixer.…”
Section: Methodsmentioning
confidence: 99%
“…It has a long history of use not only as a food but also as a medicine, and it is an important source of marine drugs. Dong et al (2021) [ 13 ] found that Saccharina japonica extract (SJE) by the ethyl acetate phase was rich in fucoidan polyphenols, which have a strong ability to inhibit oxidase activity and scavenge free radicals. In addition, carbohydrates such as fucoidan polysaccharides contained in SJE can synergize with polyphenols to present better antioxidant activity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that n-3 polyunsaturated fatty acids (PUFA) could downregulate the expression of interleukin (IL)-6, IL-1β, tumor necrosis factor (TNF)-α, and prostaglandin E-2, which ameliorated post-menopausal depression induced by chronic mild stress and maternal separation [ 42 ]. In addition, Saccharina japonica is a common marine vegetable in East Asia and its ethanol extract decreased the depressive symptoms of dextran sodium sulfate-induced mice by increasing anti-inflammatory cytokine and downregulating expression levels of nuclear factor kappa-B (NF-κB), NOD-like receptor 3, and Toll-like receptor-4 (TLR-4) [ 43 ]. Furthermore, apple phenolic extract improved lead acetate-induced depression-like behaviors through attenuating neuroinflammation and neuronal apoptosis, which was associated with the miR-22-3p/sirtuin 1 (SIRT1) signaling pathway [ 39 ].…”
Section: Depressionmentioning
confidence: 99%
“…Grewia asiatica berry juice could improve depressive symptoms by decreasing oxidative damage in the brain through increasing superoxide dismutase (SOD) and glutathione peroxidase (GPx) levels [ 50 ]. Another study pointed out that Saccharina japonica ethanol extract decreased the depression-like behaviors of dextran sodium sulfate-induced mice by increasing the activity of SOD [ 43 ]. In addition, maqui berries had an anti-depressive effect against post-stroke depression by upregulating expression levels of reduced glutathione (GSH) and enhancing the activities of SOD and catalase (CAT) [ 51 ].…”
Section: Depressionmentioning
confidence: 99%